Risk Identification and Mitigation in Entrepreneurship - Sulfiani, Sulfiani; Herman, Herman; Kamaruddin, Syamsu A. (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research examines the main risks that entrepreneurs often face, namely financial, operational and market risks, as well as strategies to reduce the impact of these risks. Financial risks include unstable cash flow problems and limited capital which can affect the smooth running of the business. Operational risks include problems in the supply chain, human error, and equipment failure that can disrupt business activities. Meanwhile, market risks are related to changes in consumer interests, competition and changing trends. The method used in this research is in-depth interviews with ten small and medium enterprise (SME) owners in various sectors, as well as a literature review from various sources. The results show that several strategies are effective in addressing these risks. For example, for financial risks, cash flow planning and reserve funds help entrepreneurs deal with financial fluctuations. In terms of operational risks, having backup suppliers and providing regular training to employees can reduce disruptions in production. Finally, for market risks, product innovation and regular consumer surveys help businesses stay relevant and competitive. This research concludes that identifying and mitigating risks from the start can increase business resilience to various challenges. These findings are expected to help business owners to manage risks and make their businesses stronger.